Assessing protein distribution and dendritic spine morphology relationships using structured illumination microscopy in cultured neurons - Kathryn J. Bjornson; Michael E. Cahill (STAR Protocols, 2024)
Summary: Dendritic spines are protrusions on dendrites forming the postsynaptic aspect of excitatory connections within the brain. Spine morphology is associated with synaptic functional strength and the spatial regulation of protein nanodomains within dendritic spines is an important determinant of spine structure and function. Here, we present a protocol to resolve the nanoscale localization of proteins within dendritic spines using structured illumination microscopy. We describe steps for the structural analysis of dendritic spine parameters, protein localization analysis, and data processing.For complete details on the use and execution of this protocol, please refer to Bjornson et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.